2018
DOI: 10.1002/hrdq.21306
|View full text |Cite
|
Sign up to set email alerts
|

Building employee resilience through wellbeing in organizations

Abstract: The resilience of employees has been recently identified as essential to organizational adaptability in uncertain and dynamic business environments. Yet little is known about how the resilience of employees can be developed. The present study investigated the effect of a wellbeing intervention on two forms of individual resilience: employees' stress‐coping ability (personal resilience) and resilient workplace behaviors (employee resilience). All participants (n = 209) completed an online wellbeing and resilien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(146 citation statements)
references
References 70 publications
8
124
1
1
Order By: Relevance
“…One's career sustainability and employability are strongly related to the way in which individuals utilize their resources and proactively shape their careers [32]. Results from empirical research on resilience in the workplace [33,34] showed the role played by some key resources in protecting and promoting health, well-being, and performance from an organizational positive psychology perspective [34][35][36][37][38]. Literature about resilience [39] stated how, to be effective, resources must be sufficiently robust, redundant, or rapid to buffer or counteract the effects of stressors [40] resulting, as a whole, in a set of adequate adaptive capacities.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…One's career sustainability and employability are strongly related to the way in which individuals utilize their resources and proactively shape their careers [32]. Results from empirical research on resilience in the workplace [33,34] showed the role played by some key resources in protecting and promoting health, well-being, and performance from an organizational positive psychology perspective [34][35][36][37][38]. Literature about resilience [39] stated how, to be effective, resources must be sufficiently robust, redundant, or rapid to buffer or counteract the effects of stressors [40] resulting, as a whole, in a set of adequate adaptive capacities.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Vanhove, Herian, Perez, Harms, and Lester's () meta‐analytical study summarized the effects of resilience‐training programs and found that they have positive effects on the psychological and physical health of employees in the short term but that the effects gradually dissipated over the long term. Tonkin, Malinen, Näswall, and Kuntz () argue that individual resilience can be developed by understanding and investigating the constantly changing external environment.…”
Section: Workforce Resilience and Human‐resource Developmentmentioning
confidence: 99%
“…Birey boyutu, çalışanların "resilience" kapasitesi olarak da ifade edilebilecek olan çalışan "resilience"ı (employee resilience) olarak yazında kullanılmaktadır. Çalışan "resilience"ı psikoloji ve örgütsel davranış alanında özellikle 2010 sonrası sıklıkla incelenmeye başlanan bir olgudur (Cooke,Cooper, Bartram, Wang, ve Mei, 2016;Tonkin, Malinen, Näswall, ve Kuntz, 2018).…”
Section: İlişkilerin Hayatta Kalması (Sağ Kalım-survival) Karşılıklunclassified